The Legality of Inclusion of The Indonesian National Arbitration Board as The Responsible Responsible in The Application for Announcement of The Arbitration Award - Habibullah Alfarizi P.R.; Mutiara Bella Alfianti; Siti Khamidah; Desya Septya Mulyana (Westscience Press, 2026)
This study is motivated by the recurring practice of naming the Indonesian National Arbitration Board (BANI) as the Respondent in applications for the annulment of arbitral awards, despite being inconsistent with Law Number 30 of 1999 and Supreme Court Regulation Number 3 of 2023. This research aims to examine the limits of the District Court's authority in reviewing applications for annulment of arbitral awards and to determine whether judgments imposing liability on BANI may be classified as ultra vires. The findings indicate that the District Court's authority is limited to examining the statutory grounds for annulment under Article 70 of the Arbitration Law. The inclusion of BANI as a respondent constitutes an error in person, while any judgment imposing liability on BANI exceeds the court's legal authority and therefore may be classified as an ultra vires decision.